2009
DOI: 10.3141/2103-01
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the Highway Safety Manual's Accident Prediction Model for Italian Secondary Road Network

Abstract: The forthcoming first edition of the Highway Safety Manual (HSM) will introduce safety predictive models both for road segments and intersections. A key issue for allowing HSM to become a standard for road owners and managers worldwide is the transferability of the predictive models to different networks. The application of the calibration procedure of the HSM model to different countries has been evaluated, with all practical and potential application problems outlined. In this study, the calibration procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 5 publications
0
22
0
2
Order By: Relevance
“…In particular, the HSM predictive method was assumed as a benchmark by several studies, which calibrated it for different areas [42][43][44][45][46][47][48]. Some of them clearly concluded that locally-derived functions fits better data than the calibration of other functions.…”
Section: Transferability Of Predictive Methodsmentioning
confidence: 99%
“…In particular, the HSM predictive method was assumed as a benchmark by several studies, which calibrated it for different areas [42][43][44][45][46][47][48]. Some of them clearly concluded that locally-derived functions fits better data than the calibration of other functions.…”
Section: Transferability Of Predictive Methodsmentioning
confidence: 99%
“…Finally, other researchers have examined the applicability of the IHSDM within and outside of the US, as well as its calibration scope (Bansen & Passetti, 2005; Dominguez-Lira, Castro, Pardillo-Mayora, & Gascó n-Varó n, 2010; Donnell, Gross, Stodart, & Opiela, 2009;Koorey, 2010;Marchionna, Perco, & Falconetti, 2012;Martinelli, La Torre, & Vadi, 2009). Donnell et al (2009) provided recommendations on the need to expand the capabilities of the IHSDM's design consistency module to consider low-speed, complex alignments.…”
Section: Introductionmentioning
confidence: 99%
“…However, the most demanding and challenging part of this effort has been linked to data collection, especially in intersections, due to its complexity. Another point to be highlighted is the fact that several studies began investigating two lane highways, because their importance in rural areas (Banihashemi, 2011;Barber, 2014;Koorey, 2010;Lubliner, 2011;Martinelli et al, 2009;Metha & Lou, 2013;Saito et al, 2011;Silva, 2012;Srinivasan et al, 2011;Sun et al, 2006;Williamson & Zhou, 2012;Xie et al, 2011). A synthesis of the current situation in two lane highways segments is shown in the Table 2.1.…”
Section: Crash Prediction Modelsmentioning
confidence: 99%
“…Also, the calibration procedure was evaluated in Italy. It has been applied to highways in Arezzo and some potential problems related to transferability of this methodology were outlined (Martinelli, La Torre, & Vadi, 2009 …”
Section: ____________________________________________________________mentioning
confidence: 99%